TIPE NEGOSIASI YANG DIGUNAKAN OLEH MAHASISWA DALAM PRAKTEK COMPLAIN HANDLING - Danendra Putra Nyoman; Budiada Kadek (Maha Widya Duta : Jurnal Penerangan Agama, Pariwisata Budaya, dan Ilmu Komunikasi, 2018)
An important concept that forms the basis of customer loyalty in the tourism industry is customer satisfaction. One of the things that can cause customer satisfaction is how a tourism service provider responds to customer complaints. This study aims to describe several types of negotiations and the tendencies of student negotiation style of students in Cultural Tourism Study of Mpu Kuturan State Institute of Hindu. To answer these issues, observation methods, literature studies and interview methods were used. The results of these methods can be described as follows. There are 4 types of negotiations when dealing with customers based on Corvette (2014). The four types of negotiations are Avoidance, Adversarial, Accommodating and Cooperative. Based on the results of the study 30% of students did avoidance technique. As many as 60% of students do accommodating technique, the other 10% do cooperative techniques and no students do adversarial techniques. The results of this study are expected to be the basis for teaching student, especially in applying the right concept of negotiation styles at the right time. Keywords: Negotiations, Complain Handling.